2022
DOI: 10.5851/kosfa.2022.e34
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Vacuum Packaging of Hot-Boned Lamb at Early Postmortem Time on Meat Quality during Postmortem Chilled Storage

Abstract: To evaluate the effects of early postmortem vacuum packaging (VP) on meat quality during postmortem chilled storage, hot-boned lamb was vacuum-packaged at 1, 6, 12, 24, and 48 h postmortem and stored around 2°C until 168 h postmortem, with lamb packaged in plastic wrap as the control (aerobic packaging). Intramuscular pH decline was delayed when lamb was vacuum packaged at 1, 6, and 12 h postmortem (p<0.05). The lamb vacuum-packaged at 1 h postmortem (VP-1h group) had significantly lower shear force values and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…However, as this study was a review of previous research within a relatively limited field, concluding that its results represent global research trends in the field of animal agriculture and food may be difficult; hence, continuous monitoring through additional follow-up studies is warranted. [110], [111], [112], [113], [114], [115], [116] Malt Genomic DNA; inflammation; Pediococcus acidilactici; periodontitis; Porphyromonas gingivalis [106] Meat Gut microbiota; meat; protein digestion; proteolytic enzyme; sous-vide [117] Meat products Authentication; essential oils; lipidomics; liquid chromatography-mass spectrometry; low-salt meat products; low-sodium meat products; meat product; metabolomics; nanoemulsion; natural preservative; natural salt replacers; salt alternatives; salt-modifying; salt reduction [118], [119], [120] Meat water-holding capacity; whey; whey protein; whipping cream; whipping property; yogurt [122], [123], [124], [125], [126], [127], [128], [129], [130], [131], [132], [133],…”
Section: Discussionmentioning
confidence: 99%
“…However, as this study was a review of previous research within a relatively limited field, concluding that its results represent global research trends in the field of animal agriculture and food may be difficult; hence, continuous monitoring through additional follow-up studies is warranted. [110], [111], [112], [113], [114], [115], [116] Malt Genomic DNA; inflammation; Pediococcus acidilactici; periodontitis; Porphyromonas gingivalis [106] Meat Gut microbiota; meat; protein digestion; proteolytic enzyme; sous-vide [117] Meat products Authentication; essential oils; lipidomics; liquid chromatography-mass spectrometry; low-salt meat products; low-sodium meat products; meat product; metabolomics; nanoemulsion; natural preservative; natural salt replacers; salt alternatives; salt-modifying; salt reduction [118], [119], [120] Meat water-holding capacity; whey; whey protein; whipping cream; whipping property; yogurt [122], [123], [124], [125], [126], [127], [128], [129], [130], [131], [132], [133],…”
Section: Discussionmentioning
confidence: 99%
“…Further, the LTL is a very long muscle attached from the thoracic to the lumbar vertebrae. Thus, when sampling the LTL muscle, the thoracic (LT) region (ribeye cut) and the lumbar (LL) region (strip loin cut) are classified separately [ 35 - 37 ]. As shown in Fig.…”
Section: Comparison Of Muscle Fiber Characteristics Between Different...mentioning
confidence: 99%
“…For example, when refrigerating or freezing pork, taking into consideration the histological and physicochemical characteristics of each meat part can improve meat quality or prevent quality deterioration [ 9 , 10 ]. In general, considerable effort is being made to identify excellent technologies for packaging and storing (aging) meat [ 35 , 40 - 42 ], and a deeper understanding of the muscle fiber characteristics of each muscle type or meat cut will make this process easier. Previous studies conducted from this perspective have shown that FG muscle fibers are more vulnerable to freezing than SO muscle fibers [ 9 , 10 ].…”
Section: Post-harvest Strategies For Controlling Meat Qualitymentioning
confidence: 99%
“…Proteolysis is a major factor in improving meat quality traits such as tenderness and WHC [ 26 , 27 ]. Several factors influence the rate and extent of proteolysis such as species, breed, animal age, diet, individual muscle, marbling content, and aging method [ 17 , 28 31 ]. The effect of aging on the tenderness of beef has long been studied, and many theories have emerged, such as those related to calpain, calcium ion, and cathepsin [ 32 ].…”
Section: Mechanism Of Postmortem Aging On Changes In Meat Qualitymentioning
confidence: 99%